Trisomy 1q24----1q41 in two sibs with an insertion in an inverted chromosome 4. Issue 2 (April 1984) - Stoll, C; Roth, M P; Dott, B
Abstract : We report two patients whose karyotype revealed an additional segment 1q inserted into an inverted chromosome 4. The patients were partially trisomic for the region 1q24----1q41, karyotype 46, XY or XX, inv ins(4;1)inv(4)(q28;q24q41)(p15 . 3q28), while in the mother the chromosomal aberration was balanced. The inserted segment was inverted. In six patients from three other families with insertions, the segment 1q25----1q32 was inserted into the short arm of chromosome 1. In another patient, the segment 1q25----1q42 of the mother was inverted and inserted into the long arm of chromosome 6. These findings suggest an increased susceptibility for a segment of the long arm of chromosome 1 to be inserted and inverted in rearrangements.